Travelling along the Clinical Roadmap: Developing Electrospun Scaffolds for Tendon Repair. (23rd March 2014) - Bosworth, Lucy A.
Abstract : Biopolymers, such as poly( ε -caprolactone), can be easily electrospun to create fibrous scaffolds. It is also possible to control the alignment of the emitted fibres and further manipulate these scaffolds to create 3D yarn structures, which resemble part of the tendon tissue hierarchy. Material properties, such as tensile strength, can be tailored depending on the selection and combination of polymer and solvent used during electrospinning. The scaffolds have been proven to separately support the adhesion and proliferation of equine tendon fibroblasts and human mesenchymal stem cells whilst simultaneously directing cell orientation, which caused their alignment parallel to the underlying fibres. Implantation of scaffolds into the flexor digitorum profundus tendon of mice hindpaws yielded encouraging results with minimal inflammatory reaction and observation of cell infiltration into the scaffold. This research demonstrates the progression of electrospun fibres along the clinical roadmap towards becoming a future medical device for the treatment of tendon injuries.